Eﬀect of the combination of theophylline and budesonide on production of proinﬂammatory cytokines by blood cells of patients with chronic obstructive pulmonary disease - A. G. Kadushkin; A. D. Taganovich; L. V. Movchan; E. I. Talabaeva; A. V. Plastinina; T. V. Shman (Туберкулез и болезни лёгких)
The objective: to evaluate the ability of the combination of theophylline and budesonide to suppress proinﬂammatory cytokine production byblood cells in patients with chronic obstructive pulmonary disease (COPD).Subjects and Methods. Peripheral blood mononuclear cells (PBMCs) or whole blood cells of COPD patients (n = 27) were incubated with budesonide (10 nM), theophylline (1 μM), or the combination thereof and stimulated with phytohemagglutinin (PHA) or phorbol myristate acetate (PMA) and ionomycin. The enzyme immunoassay was used to evaluate the secretion of thymic stromal lymphopoietin (TSLP), macrophage migration inhibitory factor (MIF), interleukin 17A (IL-17A), IL-33, and other mediators of PBMC cells, and induced PHA. The ﬂow cytometry was used to analyze intracellular production of proinﬂammatory cytokines stimulated by PMA/ionomycin in T-helpers (CD4+) and cytotoxic T-lymphocytes (CD8+).Results. Theophylline reduced the secretion of IL-4 and IL-17A by PBMC cells. The combination of budesonide with theophylline inhibited the synthesis of IL-4, IL-5, IL-8, IL-13, IL-17A, IL-33, TSLP, MIF by PBMC cells as well as the production of IL-4, IL-8, tumor necrosis factor-α, and interferon-γ by cytotoxic T-lymphocytes and T-helpers. The combination of theophylline and budesonide had a more pronounced inhibitory eﬀect on the production of IL-4 and IL-8 by PBMC cells as well as the synthesis of IL-4 by CD4+ T-cells and IL8 by CD8+ T-lymphocytes versus the eﬀect of monotherapy with budesonide.